Ribā al-Nasī’ah in Gold Transactions: Qur'anic Exegesis of the Antam Case - Muhammad Nurul Alim; Irwan Maulana; Adam Rizki; Aam Slamet Rusydiana (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) ZAD, 2026)
This study examines the gold trading dispute between Budi Said and PT Aneka Tambang tbk from the perspective of the Qur'an and Islamic economic perspective, with particular emphasis on the concept of ribā al-nasī’ah. The case centers on a documented discrepancy involving 1,136 kilograms of gold arising from a deferred-delivery sales contract in which payment was made in full upfront, while the physical delivery of the gold was carried out in in stages over an extended period. an extended period, from a total transaction valued at approximately IDR 3.5 trillion. The case centers on a documented discrepancy involving 1,136 kilograms of gold arising from a deferred-delivery sales contract in which payment was made in full upfront, while the physical delivery of the gold was carried out. The total value of the transaction was approximately IDR 3.5 trillion. The contractual arrangement—characterized by advance payment, delayed and non-simultaneous delivery, and non-transparent discount mechanisms — raises complex legal and ethical questions under Islamic commercial law. This research employs a qualitative library-based methodology that integrates normative-juridical analysis, Qur’anic exegesis (tafsīr taḥlīlī and tafsīr mawḍū’ī), and maqāṣid al-sharī’ah analysis. The study draws upon data from judicial decisions, including Supreme Court Cassation No. 1666 K/Pdt/2022 and Surabaya District Court No. 158/Pdt.G/2020/PN.Sby., as well as official case reports and both classical and contemporary Islamic jurisprudential literature. The findings demonstrate that the transaction structure violates the principle of yadan bi yadin (immediate mutual possession) and constitutes ribā al-nasī’ah due to the deferral of gold delivery beyond the time of payment. Furthermore, the lack of transparency in the discount mechanisms introduce elements of gharar (uncertainty) and represents a breach of amānah. These violations produced multidimensional consequences, including a judicially verified material loss of IDR 817,465,600,000, legal sanctions, reputational damage, and a decline in institutional trust. The novelty of this study lies in its integrative application of Qur’anic exegesis alongside case-specific juridical analysis to demonstrate that classical Sharī‘ah principles governing commercial transactions remain highly relevant and operationally applicable to contemporary large-scale institutional transactions.